Citizenship and migration. Globalization and the politics of belonging - CASTLES, Stephen (Macmillan Publishing Company, 2000)
Linking key debates about citizenship with discussions about migration and ethnicity, Citizenship and Migration examines the new challenges globalization is creating throughout the world. As boundaries are being blurred and nation-state powers eroded, millions of people have multiple citizenship and millions more lack citizenship of their country of residence. Increasing numbers of citizens do not belong, thus undermining the national state as the central site of democracy. Particularly attentive to the impact of globalization on the conventional, legal definitions of citizenship, this study also recognizes that global integration has unleashed strong forces of multiculturalism.